Impact of post-match fatigue on peak force in elite youth soccer players: Analysis of 48 to 72 hours post-match using the isometric mid-thigh pull exercise - Pimenta, Ricardo; Cunha, Lúcio; Nakamura, Fábio Yuzo (Biology of Sport, 2025)
This study aimed to evaluate the time-course of the recovery of force-generating capacity in young adult soccer players post-match. Seventy-three Under-19 and Under-23 soccer players were assessed using the isometric mid-thigh pull (IMTP) test. Measurements were taken during a baseline session (under non-fatigued conditions) and at 48 h and 72 h post-match. External and internal load metrics were recorded on match day and training days using a Global Positioning System and the session session-rating of perceived exertion, respectively. For each game, players’ observations were divided into experimental and control conditions, reflecting playing more than 60 minutes and 0 minutes of match participation, respectively. Within-subject correlations between selected external match load metrics and internal load, and changes in IMTP peak force (PF), were analyzed for players in the experimental condition. The results demonstrated that, in the experimental condition, the IMTP PF was impaired by 8.1% at 48 h post-match ( p < 0.001, d = 0.72) and 6.2% at 72 h post-match ( p < 0.001, d = 0.68), with no significant differences between 48 h and 72 h post-match ( p > 0.05). However, no correlations were observed between changes in IMTP PF at 48 h and 72 h post-match and either external or internal load. Moreover, an 8.2% reduction in IMTP peak force from baseline to 72 h post-match (1603N vs 1471N, p = 0.01, d = 0.46) was observed in the control condition, which can be attributed to the load on MD+2. This finding suggests that the IMTP is a sensitive test for detecting fluctuations in the recovery of force-generating capacity, further highlighting that soccer players do not achieve full recovery in this test within the specified time frame.